CHEMICAL CHARACTERIZATION AND FREE RADICAL SCAVENGING ACTIVITY OF DENDROBIUM THONGCHAI EXTRACTS: A PROMISING SOURCE FOR NEUROPROTECTIVE AND ANTIMICROBIAL AGENTS - VANATHI SUNDARAPANDIYAN; ANAND SP; KARTHICK S; SUBASRI K (Asian Journal of Pharmaceutical and Clinical Research, 2026)
Objectives: This study assessed the potential of Dendrobium thongchai (gold) root extracts as sources of neuroprotective and antimicrobial compounds by characterizing their phytochemical constituents and antioxidant activity. Methods: Methanol and ethanol were used to macerate root powders, and the extraction yield was quantified using gravimetric analysis. Gas chromatography-mass spectrometry analyzed the methanolic (MeOH) extract, identifying compounds based on National Institute of Standards and Technology (NIST) library matches. Ferric reducing antioxidant power (FRAP) and 2,2-diphenyl-1-picrylhydrazyl assays measured antioxidant activity at five concentrations (0.8–4.0 mg/mL). Each assay was performed in triplicate, with statistical analysis using one-way analysis of variance and Tukey’s post hoc test to determine significant differences (p<0.05). Results: Gas chromatography-mass spectrometry (GC-MS) profiling of the MeOH extract identified 45–47 compounds, including indole derivatives, fatty acid esters, alkaloids, and glycosides. Several metabolites showed moderate to strong NIST match factors, indicating antioxidant and neuroprotective potential, such as indole, 3-[2-(3-methylphenyl)ethenyl]-, oleic acid eicosyl ester, and an α-tocopherol derivative. Antioxidant assays showed concentration-dependent activity in both extracts; the ethanolic extract showed higher radical scavenging efficiency (IC50=3.43±0.12 mg/mL) compared to the MeOH extract (IC50=3.74±0.09 mg/mL). FRAP results confirmed ethanol as more effective for phenolic extraction. Conclusion: This analysis reveals the chemical diversity and antioxidant properties of D. thongchai (gold). The presence of indole and glycosidic compounds suggests neuroprotective and antimicrobial potential, positioning this orchid for phytopharmaceutical research. Further work is needed to isolate and validate bioactive constituents using advanced analytical and biological assays.